Peningkatan Kemampuan Maharatul Istima’ Menggunakan Metode Audio Visual di Pondok Pesantren - Amatullah Fauziyah (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2023)
Maharatul Istima’ (listening skill) is one of the four core skills in Arabic language learning. The delivery of Maharatul Istima’ can employ various methods, one of the commonly used being the audio-visual method. The aim of this study is to improve the Maharatul Istima’ abilities of female students (santriwati) through the use of the audio-visual method. The research method used is Classroom Action Research (CAR), which was conducted over two cycles.Each cycle consisted of four stages: planning, implementation of action, observation, and reflection. In Cycle I, 27 out of 30 students scored below 65, with the highest score being 76 and the class average at 59.36. In Cycle II, the lowest score improved to 65, and the highest score reached 90, with the class average rising to 79.1. Based on the results, it can be concluded that the use of audio-visual media shows notable progress in enhancing the Maharatul Istima’ skills of the students.